Effect of Moderate Red Wine versus Vodka Consumption on Inflammatory Markers Related to Cardiovascular Disease Risk: A Randomized Crossover Study. (17th August 2020) - Wotherspoon, Amy; Elshahat, Sarah; McAlinden, Nicholas; Dean, Katrina; Young, Ian S.; Sharpe, Peter C.; Blankenburg, Stefan; Patterson, Chris C.; McKinley, Michelle C.; Evans, Alun; Woodside, Jayne V.
Abstract: Objective: Few interventions have tested the effects of different alcohol types on cardiovascular risk biomarkers. The aim of this study was to investigate the effects of red wine versus vodka on inflammatory and vascular health-related biomarkers. Methods: In a crossover study, participants were randomized to receive either red wine or vodka (3 units/day) for 2 weeks. Following a 2-week washout period, participants then consumed the alternate alcoholic drink for 2 weeks. Fasting blood samples were collected just prior to and at the end of each 2-week period. A total of 13 inflammatory and vascular health biomarkers were assessed. Results: A total of 77 of 85 recruited healthy men completed the study. Leptin levels were significantly raised after each intervention ( p  ≤ 0.01). APO A1 significantly increased following vodka, but not red wine, intervention ( p ≤  0.01). A significant difference between the interventions was noted for adiponectin only ( p  ≤ 0.01), although neither of the within-group changes were statistically significant ( p  > 0.01). Conclusions: The current study found significantly increased levels of leptin following both red wine and vodka consumption, increased levels of APO A1 following vodka consumption, and significant difference between both interventions for adiponectin only. Further studies are needed to investigate the effects of longer-term alcohol consumption on inflammatory and vascular health biomarkers.